Management of Teaching Factory Program Implementation to Increase Absorption Rate Labor in the Business World and the Industrial World - Wahyudin, Wahyudin (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This research is motivated by the weakness of vocational high school graduates who have not been widely absorbed by the business and industrial world in West Java. The general aim of this research is to obtain an overview and analyze the management of implementing the teaching factory program in increasing the employment rate in the business and industrial world at vocational schools. This research specifically aims to describe and analyze: 1) Planning the teaching factory program; 2) Organizing the teaching factory program; 3) Implementation of the teaching factory program; and 4) Supervision of the teaching factory program. This research uses a qualitative approach with a case study. Data collection techniques in this research were carried out through interviews, observation and document study. The results of this research show the following: 1) The planning of the teaching factory program has been planned based on the vocational school teaching factory program planning guidelines; 2) The organization of the teaching factory program has been organized based on the main tasks and functions of the vocational school; 3) The implementation of the teaching factory program is carried out in accordance with the teaching factory guidelines from the Directorate of Vocational Schools, but in the product and service aspects there are still some weaknesses; and 4) Supervision of the teaching factory program was found to have been supervised with reference to the supervision aspects determined by the Vocational School Directorate. The conclusions from this research show that the management of implementing the teaching factory program in Vocational High Schools is able to absorb graduates to work and have competencies in accordance with the demands of the business and the industrial worlds, but it is still found that in several schools this teaching factory program has not been able to be implemented due to limited facilities and infrastructure that demands to have such standards in companies and industries.